Drivers of changing cropping patterns in Nepal: A review - Oli, Lal Bahadur (The Third Pole: Journal of Geography Education, 2023)
This paper reviews various aspects of drivers of changing cropping patterns in Nepal based on secondary data sources. Data were acquired from Google Scholar and Research Gate database 32 relevant professional journal articles in between 2000-2022 were intensively reviewed. The drivers of changing cropping patterns are complex and interrelated in the farming system. Spatial analysis of cropping patterns of different geographical scales shows that cropping pattern is an integral part of a behavioral focus to reflect the space relation of the community people. The drivers of changing cropping patterns are numerous and intricately linked. It is challenging to gauge the relative significance of the effects ascribed to each scale of the driver or the interactions between them at any particular geographic region. The study revealed that there are several types of drivers for changing cropping patterns. Among these various types of drivers, the theme of technological advancement/inputs, climate change, infrastructural development, road connectivity, and market demand play prominent roles in changing cropping patterns however other drivers such as off-farm employment, agriculture service extension/training, government policies, population growth/change/migration (rural to urban; international.), are also remarkable in this studies. In the Nepalese context, this study indicates that the more prominent role playing drivers of changing cropping patterns are technological advancement /inputs, infrastructural development and road connectivity, and market demand and climate change however land degradation and government policies also play a role to shifting cropping patterns. These all drivers interact and link with each other, leading to changing cropping patterns in Nepal.